Avaliação de eficiência da estação de tratamento de esgoto ERQ Oeste Aracaju/SE - Andrade, Higor Azevedo (2022)
The treatment of domestic sewage is something that should be encouraged in the country, the incorrect disposal of effluent causes problems for both the environment and the health of the population. To prevent this from happening, sewage treatment plants must be constructed for the correct disposal of sewage, minimizing the consequences of its release back to nature, meeting the standards set by CONAMA Resolution 430. This work aims to evaluate the activities ERQ West Sewage Treatment Station, operating area under the responsibility of the Sergipe Sanitation Company (DESO), analyzing the efficiency of each treatment step and verifying compliance with environmental legislation. Eight collections were performed at the station, to evaluate the parameters of each UASB unit, as well as the oxidation ditch. The parameters evaluated in this work were pH, turbidity, flow, sedimentable solids, totals solids and COD. Through the obtained results, it was possible to verify that the affluent flow agrees with the defined in project, not being a station with oversizing problems. Regarding the efficiency of the station in terms of COD removal, it presented values of 64.2% when compared to raw sewage values, a value lower than that used for sizing (85.4%), but the average BOD value final converted was within that limited by environmental legislation. It was also possible to observe the influence of parasitic contribution of rainwater in the system, showing decrease of the tributary organic load in the rainy periods that the city of Aracaju passed during the study.